IMPLEMENTASI TEORI BELAJAR HUMANISTIK PADA PEMBELAJARAN PAI DALAM MENINGKATKAN PRESTASI PESERTA DIDIK - Istifaur Rosidah; Robbiah Ratna Swari Hibbatullah (Al-Kindi, 2025)
This study aims to examine the implementation of humanistic learning theory in Islamic Religious Education (PAI) as an effort to improve student achievement. Humanistic learning theory emphasizes the holistic development of individuals cognitive, affective, and psychomotor aspects by prioritizing respect for students' feelings, experiences, and needs. This approach views learners as active subjects in the learning process who can develop optimally when given space, trust, and intrinsic motivation. This research employs a descriptive qualitative method, with data collected through observation, interviews, and document analysis. The findings show that the application of humanistic learning theory in PAI creates a more enjoyable, open, and participatory learning environment. Teachers act as facilitators, guiding students to discover meaningful learning that relates to their real-life experiences. This implementation positively impacts students’ learning motivation, understanding of religious material, and academic achievement. Therefore, integrating humanistic theory into PAI instruction is highly relevant for fostering student-centered education and addressing the need for meaningful and holistic learning.